Prognostic and Predicted Significance of FENDRR in Colon and Rectum Adenocarcinoma - Yang, Fan; Sun, Siyu; Yang, Fei (Frontiers in Oncology, 2021)
Background The role of fetal-lethal non-coding developmental regulatory RNA (FENDRR) has been explored in various cancers; however, its relationship with colon adenocarcinoma/rectum adenocarcinoma (COAD/READ) remains unclear. The objectives of this study were to identify and assess any associations between FENDRR and COAD/READ using The Cancer Genome Atlas (TCGA) database and the Genetic Data Commons (GDC) Data Portal. Methods The records of patients with COAD/READ were collected from the GDC Data Portal. After comparing the expression level of FENDRR in COAD/READ and healthy tissues, we evaluated the association of FENDRR with clinicopathological characters and the survival rate, the impact of FENDRR on prognosis, the biological function of FENDRR, and the relative abundance of tumor-infiltrating immune cells in patients with COAD/READ. Moreover, we aimed to construct a protein-protein interaction (PPI) network for selecting genes and a ceRNA network for presenting mRNA-miRNA-lncRNA interactions. Results In patients with COAD/READ, FENDRR expression could differentiate tumor tissues from the adjacent healthy tissues since it was significantly lower in the former than in the latter. High FENDRR expression was correlated with poorer survival and higher tumor stage, current tumor stage, and metastasis stage, and also exhibited high scores for apoptosis, autophagy, and senescence. Immune cell infiltration analysis showed that the high expression group had significantly lower immune and stromal scores. Low FENDRR expression was correlated with poor overall survival (OS), and thus, it could serve as an independent risk factor. The prognostic models constructed in the study performed well for the prediction of OS and disease-specific survival (DFS) using FENDRR expression. Gene set enrichment analysis revealed that vascular smooth muscle contraction, melanogenesis, basal cell carcinoma, and Hedgehog signaling pathways were significantly enriched in patients with high FENDRR expression. Eight hub genes, namely, PKM, ALDOA, PFKP, ALDOC, PYGL, CTNNB1, PSMA5, and WNT5A, were selected from the PPI network, and a ceRNA network was constructed based on the differentially expressed mRNAs, miRNAs, and lncRNAs to illustrate their regulatory relationships. Conclusion FENDRR may serve as a potential biomarker for the diagnosis and prognosis of COAD/READ.